Automation of pedestrian tracking in a crowded situation using an angled uncalibrated camera - SAMAN, SAADAT (Archīum Ateneo, 2011)
Studies on pedestrians using microscopic simulation requires large amounts of trajectory data from real-world pedestrian crowds. The collection of such data, if done manually, involves tremendous effort and is very time-consuming. Although many studies ha